Student feedback apparatuses in higher education: an agential realist analysis. Issue 3 (3rd May 2020) - Thiel, Jonas
ABSTRACT: This paper shows how Karen Barad's agential realism provides a powerful analytical framework for assessing higher education accountability. It takes the example of the UK 'National Student Survey' (NSS), a questionnaire, which purports to ascertain student course satisfaction in universities. The paper demonstrates how agential realism offers the opportunity to make visible (and theorise) three suggested effects of the NSS: (i) affective dimensions of lecturer experience; (ii) boundary creations between lecturers and students; and (iii) the marginalisation of experimental conceptualisations of practice. Analysing narrative data from six university lecturers, it will be shown how agential realism has a capacity to theorise the sociological realms of classroom encounters, institutional practices and national policy in their very entanglement. That is, university lecturers' practice is analysed as 'apparatuses of bodily production' that are enfolded into larger institutional and national apparatuses.